ANALISIS PENGARUH KUALITAS SUMBER DAYA MANUSIA, KOMUNIKASI, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. ALEXA MEDIKA MEDAN - Simbolon, Sahat (UNIKA Santo Thomas, 2021)
The purpose of this study is to describe the influence of the quality of human resources, communication, and work motivation on employee performance at PT Alexa Medika Medan. This research was conducted at PT. Alexa Medika Medan which lasts for 5 (five) months, starting from May 2019 to September 2019.This research uses nonprobability sampling method. The population in this study were employees at PT. AlexaMedika Medan as many as 83 people. Determination of the number of samples using Sugiyono's opinion, so that the total sample is all employees of PT AlexaMedika Medan, amounting to 83 people. Data collection methods in this study used a questionnaire to collect data from human resources, communication, work motivation, and employee performance variables. The analysis technique used is validity test, reliability test, descriptive analysis, classic assumption test, double regression linear analysis, double correlation coefficient linear test, partial hypothesis test or T test, simultaneous hypothesis test or F test, and coefficient determination. Descriptive analysis result for the quality of human resources and communication are good. The result of descriptive analysis for employee performance fall into the quite good category and work motivation is in not very good category. Based on partial analysis, the variable quality of human resources has a positive and significant effect on the performance of employees of PT AlexaMedika Medan, communication has a positive and significant effect on the performance of employees of PT AlexaMedika Medan, and work motivation has a positive and significant effect on the performance of employees of PT AlexaMedika Medan. Simultaneously, there is a positive and significant influence on the quality of human resources, communication, and work motivation on the performance of employees of PT AlexaMedika Medan. From the coefficient of determination that employee performance is influenced by the quality of human resources, communication, and work motivation by 58.5%. While the remaining 41.5% of employee performance is influenced by other variables not observed in this study.